2020
DOI: 10.1101/2020.04.20.052233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid and quantitative detection of COVID-19 markers in micro-liter sized samples

Abstract: COVID-19 pandemic has caused tens of thousands of deaths and is now a severe threat to global health. Clinical practice has demonstrated that the SARS-CoV-2 S1 specific antibodies and viral antigens can be used as diagnostic and prognostic markers of COVID-19. However, the popular point-of-care biomarker detection technologies, such as the lateral-flow test strips, provide only yes/no information and have very limited sensitivities. Thus, it has a high false negative rate and cannot be used for the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…In addition, Tan et al designed a microfluidic ELISA test for quantitative detection of SARS-CoV-2 S1 protein and anti-SARS-CoV-2 S1 IgG using humanized SARS-CoV-2 IgG and recombinant S1 protein, respectively. The lower LOD of 2 ng/mL for anti-SARS-CoV-2 S1 IgG and of 0.4 ng/mL for S1 antigen was achieved in serum [91]. These studies demonstrated high performance of analyzing SARS-CoV-2 specific antibodies and antigens in COVID-19 patients by microarray and microfluidic chip.…”
Section: Microarray and Microfluidic Chipmentioning
confidence: 74%
“…In addition, Tan et al designed a microfluidic ELISA test for quantitative detection of SARS-CoV-2 S1 protein and anti-SARS-CoV-2 S1 IgG using humanized SARS-CoV-2 IgG and recombinant S1 protein, respectively. The lower LOD of 2 ng/mL for anti-SARS-CoV-2 S1 IgG and of 0.4 ng/mL for S1 antigen was achieved in serum [91]. These studies demonstrated high performance of analyzing SARS-CoV-2 specific antibodies and antigens in COVID-19 patients by microarray and microfluidic chip.…”
Section: Microarray and Microfluidic Chipmentioning
confidence: 74%
“…Regression analysis yielded a Pearson’s correlation coefficient ( r ) = 0.996. d , Schematic overview of RAPPID sensors for the detection of trimeric SARS-CoV-2 spike proteins. Recently discovered antibodies 43,44 targeting distinct binding epitopes of the immunogenic spike protein were used to generate sensors in either a heteropair or homopair setup. e , f , RAPPID response curves in response to increasing concentrations of monomeric spike protein ( e ) and native trimeric spike protein ( f ) using both the heteropair (gray) and homopair (red) configuration.…”
Section: Resultsmentioning
confidence: 99%
“…LB and SB were expressed as fusion proteins with the RBD, enabling detection of all RBD-targeting antibodies. g , Ratiometric sensor response curves for neutralizing antibody 47D11 (left) 44 , and commercially available anti-spike D001 (center) and D003 (right) 43 . Insets show sensor response at low target concentrations, which allowed calculation of the limit of detection, as indicated in the graphs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the volume of the samples analyzed, Tan et al combined microfluidics and ELISA to detect IgG against different SARS-CoV-2 proteins in 10 µL serological samples within 15–20 min. However, the age of the used samples was not mentioned [ 190 , 191 ].…”
Section: Diagnostics and Biosensors For Covid-19mentioning
confidence: 99%